Faktor-Faktor yang Mempengaruhi Minat Mahasiswa untuk Menggunakan Layanan Mobile Banking di Universitas Warmadewa - Putu Lusiana Devi; I Made Sara; A.A Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2022)
The purpose of this study is to find out the effect of Benefits, Ness, and Risk of transacting on the Interests of Warmadewa University Students using Mobile Banking services both simultaneously and partially. The population of this study is active students at Warmadewa University (class of 2018-2019) a total of 100 students. This study uses multiple linear regression analysis as data analysis. From the results of the study, it can be concluded that: (1) simultaneously the benefits of mobile banking, ease of use, and risk of transacting have a significant effect on the interest of Warmadewa University Students using Mobile Banking Services. (2) Partially, Benefits, Ease of Use, Risk of Transaction significantly affect the Interest of Warmadewa University Students Using Mobile Banking Services.